(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Labor migration is a major phenomenon in Bihar, India, with millions of people migrating to other states in search of better employment opportunities and higher wages. This research paper analyzes the factors that contribute to labor migration from Bihar, its impact on the state’s economy, and the challenges faced by labor migrants.